THE IMPORTANCE OF TOURISM DEVELOPMENT - Azamatova Muxlisa Ilyos qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Tourism development is crucial for several reasons, benefiting both the industry and tourists. Sustainable development is the foundational principle for enhancing human and economic development while maintaining the functional integrity of ecological and social systems that support regional economies. Tourism has played a critical role in sustainable development in many countries and regions around the world. In developing countries, tourism development has been used as an important strategy for increasing economic growth, alleviating poverty, creating jobs, and improving food security. Many developing countries are in regions that are characterized by high levels of biological diversity, natural resources, and cultural heritage sites that attract international tourists whose local purchases generate income and support employment and economic development. Tourism has been associated with the principles of sustainable development because of its potential to support environmental protection and livelihoods.